Resposta :
Resposta:
2/7
Explicação passo a passo:
Como os denominadores são iguais basta mantê-los e operar os numeradores, assim:
3/7 - 1/7 = (3 - 1)/7 = 2/7
vamos lá
[tex] \frac{3}{7} - \frac{1}{7} = \frac{2}{7} [/tex]
good studies
![Ver imagem EDUARDOALTORIZADOALT](https://pt-static.z-dn.net/files/da1/b5eab0d099b3c154804d840210dcd91b.jpg)
Resposta:
2/7
Explicação passo a passo:
Como os denominadores são iguais basta mantê-los e operar os numeradores, assim:
3/7 - 1/7 = (3 - 1)/7 = 2/7
vamos lá
[tex] \frac{3}{7} - \frac{1}{7} = \frac{2}{7} [/tex]
good studies